亚院三年级学生使用汉语形容词 AABB 与 ABAB 重叠式的偏误分析 MISTAKES OF USING THE ADJECTIVE REDUPLICATION AABB AND ABAB BY SEMESTER VI STBA-PIA STUDENTS - Karina karina (Journal of Language, Literature and Teaching, 2021)
This study aims to examine the types of errors found in the sixth semester students of STBA-PIA, and explain the factors that cause these errors. This study used a qualitative descriptive method design. Data collection techniques were carried out by elicitation and interview techniques. The results showed that the errors in the use of reduplication of AABB and ABAB adjectives by semester VI STBA-PIA students consisted of errors of omission of 28 sentences, errors of addition of as many as 28 sentences.18 sentences, error of selection is 58 sentences and error of ordering is 7 sentences. The total errors in the use of adjective reduplication are 111 sentences. The results of the analysis also prove that the factors that cause the error are interlingual factors and intralingual factors.Keywords: Error, Adjective Reduplication, AABB, ABAB.